2017
DOI: 10.1007/s11356-017-9105-3
|View full text |Cite
|
Sign up to set email alerts
|

Putative mechanisms of genotoxicity induced by fluoride: a comprehensive review

Abstract: Genotoxicity is the ability of an agent to produce damage on the DNA molecule. Considering the strong evidence for a relationship between genetic damage and carcinogenesis, to elucidate the putative mechanisms of genotoxicity induced by fluoride are important to measure the degree of risk involved to human populations. The purpose of this article is to provide a comprehensive review on genotoxicity induced by fluoride on the basis of its mechanisms of action. In the last 10 years, all published data showed som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 44 publications
0
13
0
9
Order By: Relevance
“…Recent evidence in fish models indicated that high concentrations of fluoride can modify growth and development, induced pathologic bone deformity, and disrupt cell respiration and metabolism [15][16][17]. These events lead to an excessive production of reactive oxygen species (ROS) with resultant impairment of antioxidant system, DNA damage, mitochondrial dysfunction, and increased mortality rate [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence in fish models indicated that high concentrations of fluoride can modify growth and development, induced pathologic bone deformity, and disrupt cell respiration and metabolism [15][16][17]. These events lead to an excessive production of reactive oxygen species (ROS) with resultant impairment of antioxidant system, DNA damage, mitochondrial dysfunction, and increased mortality rate [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Although fluoride is absorbed largely by the mineralized extracellular matrix in calcified tissues, absorbed fluoride can lead to mitochondrial dysfunction, DNA damage, and lipid peroxidation in cells through the production of reactive oxygen species (ROS) [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Природа генотоксического потенциала фторид-иона, вероятно, ассоциирована с его способностью вызывать митохондриальные повреждения и оксидативный стресс [27,[63][64][65][66]68], а также ингибировать активность ферментов антиоксидантной системы [5,67]. Существуют версии о возможном влиянии фторид-иона на активность систем репарации ДНК [56], ферментов системы биотрансформации ксенобиотиков [4] или его способности запускать эпигенетические механизмы, приводящие к генотоксическим последствиям [70]. Данные гипотезы в будущем заслуживают пристального внимания.…”
Section: Discussionunclassified